FAKTOR YANG TERKAIT DENGAN JENIS PULPITIS PADA ANAK USIA SEKOLAH - Alit Suwandewi; Subahan Sanusi (Journal of Nursing Invention, 2020)
Dental and oral health is an integral part of overall health so it needs to be cultivated throughout the community. Pulpitis is a disease that commonly occurs in teeth. The purpose of this study was to determine factors associated with the type of pulpitis in school-age children in the dental clinic at the Mabu'un Health Center in Tabalong Regency. This study has a cross sectional design. The sample in this study were 31 respondents with a purposive sampling technique. Data analysis uses Chi-square test. The results of research on the most sexes with a women category was obtained 17 respondents (54.8%). The habit of brushing the most teeth with a enough category was obtained 20 respondents (64.52%). Behavior Maintenance of oral and dental health most with a enough categories was obtained by 24 respondents (77.43%). The highest incidence of pulpitis with a reversible category was obtained by 29 respondents (93.55%). There is no correlation between sex with the type of Pulpitis in school-age children. There is a correlation between the habit of brushing teeth on the type of Pulpitis in school-age children. There is a correlation between oral and dental health care behaviors towards pulpitis types in school-age children.